2014
DOI: 10.1108/jkm-10-2013-0413
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management in supporting collaborative innovation community capacity building

Abstract: Purpose – This paper aims to investigate the role of knowledge management in collaborative innovation and identifies the knowledge management approaches for supporting collaborative innovation community capacity building (CICCB) in organizations. The importance of collaborative innovation in developing organizational competitiveness is increasingly being recognized in both theory and practice worldwide. Collaborative innovation, however, is still under-explored from the trans-disciplinary persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 40 publications
0
37
0
1
Order By: Relevance
“…To reconstruct the trajectory of the project that developed green plastic, an important sustainable innovation, we organized a secondary data inventory with 295 documents, divided into: Braskem's documents (49), Scientific Articles (16), Books (4), Patents (34) and News (from newspaper and magazine websites -192).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reconstruct the trajectory of the project that developed green plastic, an important sustainable innovation, we organized a secondary data inventory with 295 documents, divided into: Braskem's documents (49), Scientific Articles (16), Books (4), Patents (34) and News (from newspaper and magazine websites -192).…”
Section: Methodsmentioning
confidence: 99%
“…Since a Resource Based View emerged in the 50's, many theoretical chains emphasized the importance of knowledge and its creation practices with fundamental elements for the survival of an organization and as an explanatory factor of differentials in business performance [32,33]. Thus, knowledge management is considered a strategy to increase business performance [34][35][36].…”
Section: Knowledge-based Dynamic Capabilitiesmentioning
confidence: 99%
“…Innovation is associated with the organization's reputation (Castilla-Polo et al, 2018). According to An, Deng, Chao, and Bai (2014), organizations need innovative processes, which can minimize costs and improve productivity, in order to survive in competitive markets. Borgen and Aarset (2016) observed that some cooperatives increased their competitiveness through collaborative innovation.…”
Section: Introductionmentioning
confidence: 99%
“…All this is achieved by providing faster and more efficient ways of solving problems, reducing some of the errors or defects in products or processes themselves, or by providing more efficient ways to achieve a certain goal. Along with these benefits, the KM also appears to have other benefits that can sometimes be more difficult to quantify, such as increasing innovation, improving customer service, increasing the speed with which products or services are introduced in the market, increasing staff motivation and involvement, promoting the ability of organizations to anticipate problems, reducing drop-out rates and staff rotation, improving the adaptation of an organization or group to its environment, facilitating the learning capacity of employees, or improving teamwork and quality on organization, to name just a few examples (Nonaka & Takeuchi, 1995;Carnerio, 2000;Gibbert et al, 2002;Zeithaml & King, 2003;Choi & Lee, 2003;Yang & Wan, 2004;Massa & Testa, 2009;Mohamed et al, 2009;Heng & Chua, 2010;Cantnera et al, 2011;An et al, 2014;Srisamran & Ractham, 2014;etc. ).…”
Section: Introductionmentioning
confidence: 99%